Laboratory Manual Instructor's Guide to Accompany Fundamental soil science - Havlin, John L. (Thomson Delmar Learning, 2006)
Fundamental Soil Science approaches the topic of soil science from the perspective of soils as dynamic, living, natural resources that affect every aspect of our lives, rather than treating soils as strictly an agricultural resource. The content assists students in understanding the many roles soils play in our environment. The authors have focused on those aspects of soil science they deem most critical for a student to know, including physical, chemical and biological properties, as well as land and soil use. Once introduced, concepts are reinforced throughout the text, leading students to more easily understand and retain the material. Following classroom learning, this will serve as a quick reference for basic soil concepts pertinent to practical experience